ANALYSIS OF ACOUSTIC COMFORT IN THE FACULTY OF SCIENCE AND TECHNOLOGY AULA NORTH SUMATRA STATE ISLAMIC UNIVERSITY MEDAN - Rosari, Ruri; Daulay, Zubair Aman; Daulay, Abdul Halim (Universitas Islam Negeri Sumatera Utara Medan, 2023)
The Hall of the Faculty of Science and Technology UINSU Medan is a multipurpose room with a volume of 477,572 m3 which is located on the lower floor of the Faculty building which is adjacent to the Faculty canteen and is often full of crowds. This research was conducted to determine the level of acoustic comfort in the room and to determine the effect of adding acoustic treatment to the front hall wall on the value of sound pressure level and reverberation time. Retrieval of data at a frequency of 125 Hz to 4000 Hz for background noise and sound pressure level, reverberation time using a sound level meter type TL200 and acoustic treatment materials from patchwork made of cotton and towels made of polyester. The results of the study showed that the absorption coefficient of the acoustic treatment material was known through testing using an acoustic box made of cardboard and the results obtained were 0.71 at a thickness of 5 cm. Obtained an average value of background noise in a closed room of 35.85 dB in an open space of 38.67 dB, an average sound pressure level value of 58.30 dB, the reverberation time value using the sabine formula is 9.244 s and in practice it is 1 ,66 s with the balloon eruption method. Treatment of cotton patchwork and polyester towels with a surface area of 7.72 m2 was given a sound pressure level of 51.19 dB and a reverberation time of 1.5 s and using the sabine formula of 1.66 s. Based on the results of this study, the addition of cotton patchwork and polyester towel treatment had an effect on reducing the value of sound pressure level and reverberation time in the hall room of the Faculty of Science and Technology, Uinsu Medan. Keywords: Sound Pressure, Reverberation Time, Patchwork.